New record of the Neotropical otter (Lontra longicaudis) in the forests of the Río Sapo basin, El Salvador - Pocasangre-Orellana, Xochilt; Álvarez, Francisco S. (Therya Notes, 2024)
The Neotropical otter Lontra longicaudis is an understudied species in El Salvador and our knowledge about it is scarce. The aim of this contribution was to record the occasional presence of L. longicaudis in the Río Sapo basin, El Salvador. The fieldwork was carried out between August and September 2022 using 20 camera traps in the Río Sapo basin. We recorded the first photographs and video of 2 individuals of L. longicaudis within the forest in the Río Sapo basin. We confirmed the occurrence of L. longicaudis in the Río Sapo basin using the forest, showing the importance of considering adjacent forests of body waters for the study and monitoring of this species.